The Economy, the Ghost in Your Gene and the Escape from Premature Mortality - Dora L. Costa; Lars Olov Bygren; Benedikt Graf; Martin Karlsson; Joseph Price (Institute of Labor Economics (IZA), 2025)
Explanations for the West's escape from premature mortality have focused on chronic malnutrition or income and on public health or state capacity. We argue that by ignoring the multigenerational effects of variance in ancestors' harvests, we are underestimating the contribution of modern economic growth to the escape from early death at older ages. Using a newly constructed multigenerational dataset for Sweden, we show that grandsons' longevity was strongly linked to spatial shocks in paternal grandfathers' yearly harvest variability when agricultural productivity was low and market integration was limited. We reason that an epigenetic mechanism is the most plausible explanation for our findings. We posit that the removal of trade barriers, improvements in transportation, and agricultural innovation reduced harvest variability. We contend that for older Swedish men (but not women) born 1830-1909 this reduction was as important as decreasing contemporaneous infectious disease rates and more important than eliminating exposure to poor harvests in-utero.
Keywords: I15; J11; N33; 330; intergenerational transmission; longevity; ecomomic growth; harvest variability